Kemampuan Aparatur Desa Dalam Pemahaman Teknologi Informasi Dan Komunikasi Menuju Electronic Desa (e- Desa) Pada Kantor Desa Kedungbocok Kecamatan Tarik Kabupaten Sidoarjo - Andika wicaksono Wicak Wicaksono; Ahmad Riyadh UB (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2018)
The study aims to analyze and describe the ability of village officials in understanding information and communication technology towards (e-Desa) in the Village Government. This type of research is descriptive qualitative. Data collection techniques were carried out through interviews with the Kedungbocok Village Apparatus supported by literature studies related to village apparatus ability. The research location at the Kedungbocok Vil- lage Office in Tarik District, Sidoarjo Regency, with consideration that the physical devel- opment in the Kedungbocok village office was fairly good in this case it was shown in the completeness of the facilities and facilities that the technology in the field was good enough. One of the interesting things to study is the ability of the village apparatus in understanding information and communication technology to the (e-Desa). The results of this study indicate that intellectual ability is still in the learning stage in understanding technology, physical ability is still in the stages of training held continuously to get the intended results, and the last cognitive abilities are still less than optimal due to the age factor of the Village Apparatus